2022
DOI: 10.1038/s41398-022-01870-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neurocognitive bases for social trait judgments of faces in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is characterized by difficulties in social processes, interactions, and communication. Yet, the neurocognitive bases underlying these difficulties are unclear. Here, we triangulated the ‘trans-diagnostic’ approach to personality, social trait judgments of faces, and neurophysiology to investigate (1) the relative position of autistic traits in a comprehensive social-affective personality space, and (2) the distinct associations between the social-affective personality dimensions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 90 publications
(82 reference statements)
0
29
0
Order By: Relevance
“…Critically, the scores for the personality factors were significantly correlated with individual tendencies in social trait judgments (as depicted in Fig. 6B) [41]. Furthermore, our trans-diagnostic approach indicates that these personality dimensions (factors) show qualitatively similar association patterns with social trait judgments from faces in both people who self-identify as ASD and those who do not.…”
Section: Individual Differences In Social Trait Judgment From Facesmentioning
confidence: 63%
See 4 more Smart Citations
“…Critically, the scores for the personality factors were significantly correlated with individual tendencies in social trait judgments (as depicted in Fig. 6B) [41]. Furthermore, our trans-diagnostic approach indicates that these personality dimensions (factors) show qualitatively similar association patterns with social trait judgments from faces in both people who self-identify as ASD and those who do not.…”
Section: Individual Differences In Social Trait Judgment From Facesmentioning
confidence: 63%
“…Using this approach, our study has revealed a connection between personality factors and social trait judgment [41]. We conducted an exploratory factor analysis on the 33 subscales from 10 established personality questionnaires related to autistic traits, affect and social deficits, prosociality (and the lack thereof), and empathy.…”
Section: Individual Differences In Social Trait Judgment From Facesmentioning
confidence: 99%
See 3 more Smart Citations